This preview shows pages 1–5. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: Chapter 5 Section 5.1 1. 1 2 3 4 0.5 1 1.5 2 2.5 3 t The function is piecewise continuous. 2. 1 2 3 4 5 0.5 1 1.5 2 2.5 3 t The function is neither continuous nor piecewise continuous. 3. 0.2 0.4 0.6 0.8 1 0.5 1 1.5 2 2.5 3 t 1 The function is continuous. 4. 0.5 1 1.5 2 0.5 1 1.5 2 2.5 3 t The function is piecewise continuous. 5. The function is of exponential order. We can take K = 3, a = 5 and M = 0. 6. Since f ( t ) = e 3 t =  f ( t )  = e 3 t , the function is of exponential order. We can take K = 1, a = 3 and M = 0. 7. Since  f ( t )  =  e 2 t sin(3 t )  e 2 t , the function is of exponential order. We can take K = 1, a = 2 and M = 0. 8. Since t 10 = e ln t 10 = e 10ln t e 10 t for all t 0, the function is of exponential order. We can take K = 1, a = 10 and M = 0. 9. cosh( t 2 ) = e t 2 + e t 2 2 is not of exponential order since for all a &gt; 0, there exists an M such that e t 2 e at for all t M . 10. Since  sin( t 4 )  1 = e t is of exponential order. We can take K = 1, a = 0 and M = 0. 11. Since 1 1 + t 1 for all t 0, the function is of exponential order. We can take K = 1, a = 0 and M = 0. 12. e t 3 is not of exponential order since for all a &gt; 0, there exists an M &gt; 0 such that e t 3 e at for all t M . 13. 2 (a) For f ( t ) = t , the Laplace transform is F ( s ) = Z e st tdt = e st t e st s 2 fl fl fl fl t =0 = 1 s 2 . (b) For f ( t ) = t 2 , the Laplace transform is F ( s ) = Z e st t 2 dt = e st s 2 t 2 + 2 e st st + 2 e st s 3 fl fl fl fl t =0 = 2 s 3 . (c) For f ( t ) = t n , the Laplace transform is F ( s ) = Z e st t n dt = n ! s n +1 . 14. For f ( t ) = t t 1 1 1 &lt; t the Laplace transform F ( s ) = Z e st f ( t ) dt = Z 1 e st tdt + Z 1 e st dt. We integrate the first integral on the righthand side by parts. In particular, we have Z t e st tdt = te st s fl fl fl fl 1 Z 1 e st s dt = e s s + 1 s Z 1 e st dt = e s s + 1 s e st s fl fl fl fl 1 = e s s e s s 2 + 1 s 2 . The second integral above can be evaluated as follows: Z 1 e st ,dt = e st s fl fl fl fl 1 = e s s . Combining these two integrals, we have F ( s ) = e s s e s s 2 + 1 s 2 + e s s = 1 s 2 e s s 2 . 15. For f ( t ) = t 1 1 1 &lt; t 2 2 &lt; t, 3 the Laplace transform is given by F ( s ) = Z 1 e st dt + Z 2 1 e st dt + Z 2 e st dt = Z 2 1 e st dt = e st s fl fl fl fl 2 1 = e 2 s s e s s = e s e 2 s s . 16. For f ( t ) = t 1 e t 1 &lt; t the Laplace transform is given by F ( s ) = Z 1 e st e t dt = Z 1 e ( s +1) t dt = e ( s +1) t ( s + 1) fl fl fl fl 1 = 0 e ( s +1) ( s + 1) = e ( s +1) s + 1 ....
View
Full
Document
This note was uploaded on 09/27/2010 for the course MATH 308 taught by Professor Comech during the Spring '08 term at Texas A&M.
 Spring '08
 comech
 Equations

Click to edit the document details